Influence of the filler matrix adhesion and the effects of conditioning on tensile properties of laser sintered parts built with polyamide glass bead dry blends - Kletetzka, Ivo; Kosanke, Maren; Meinderink, Dennis; Neßlinger, Vanessa; Grundmeier, Guido; Schmid, Hans-Joachim
Abstract In this work, the influence of the filler matrix adhesion on the tensile properties of laser-sintered parts built with Polyamide 613 filled with glass beads was investigated. For this purpose, dry blends of glass beads with and without organosilane coupling agents and polyamide powder were prepared and processed into tensile specimens on an EOS P396. The samples were tested both in the dry state and after an accelerated conditioning in a climate chamber. Furthermore, FEM simulations were performed to model the limiting cases of optimum adhesion and no adhesion. By correlating the tensile tests with the simulation results and by analyzing the fracture surfaces, it was shown that the filler matrix adhesion is sufficient in the dry state but is strongly degraded by conditioning. Even the presence of various organosilane thin films could not prevent a strong deterioration of the filler-matrix adhesion and the associated deterioration of the mechanical properties. Since a comparison with an injection molded sample of the same polymer filler combination shows identical behavior after conditioning, it is assumed that this problem is not limited to additively manufactured parts.

Tensile Testing for Polymer AM - Best Pratice at the DMRC - Kletetzka, Ivo

Influence of a prolonged shelf time on PA12 laser sintering powder and resulting part properties - Klippstein, Sven Helge; Kletetzka, Ivo; Sural, Ilknur; Schmid, Hans-Joachim (The International Journal of Advanced Manufacturing Technology)
In the laser sintering technology, the semi-crystalline polymer material is exposed to elevated temperatures during processing, which leads to serious material ageing for most materials. This has already been investigated intensively by various authors. However, the ageing of the material at ambient temperatures during shelf life has not been the focus so far. The need to analyse the shelf life can be derived from an ecological and economic point of view. This work is focusing on the shelf life of PA2200 (PA12). To reduce the potential influences of powder production fluctuations, two different powder batches stored for 5.5 years and 6.5 years are investigated and compared to a reference powder produced 0.5 years before these investigations. Multiple powder analyses and part characterisations have been performed. A significant yellowing and molecular chain length reduction can be derived from the measurement results. Whereas the influence on mechanical part performance was minor, the parts built with the stored powders are more yellowish. As it is most likely that this is due to the consumption of polyamide stabilisers, it can be assumed that these parts will be subject to significantly faster ageing. Therefore, it is still not recommended to use the stored powders for critical parts or light intense and humid environments.
Keywords: Selective laser sintering; Shelf life; Polyamide 12; powder; PA2200; material ageing

Charakterisierung und Bewertung von flammgeschützten PA12 Pulvermischungen hinsichtlich der Verarbeitbarkeit im Lasersinter-Prozess - Sajadi, Said

Clinching and resistance spot welding of thermoplastic composites with metals using inserts as joining interfaces - Troschitz, Juliane; Vorderbrüggen, Julian Heinrich Josef; Gude, Maik; Meschut, Gerson (Proceedings of the 23rd International Conference on Composite Materials (ICCM23))

A Regret Policy for the Dynamic Vehicle Routing Problem with Time Windows - Dieter, Peter (Lecture Notes in Computer Science)

Case Study IV: Individualized Medical Technology using Additive Manufacturing - Menge, Dennis; Milaege, Dennis; Hoyer, Kay-Peter; Schmid, Hans-Joachim; Schaper, Mirko (Climate Protection, Resource Efficiency, and Sustainable Engineering)

Ich lobe meinen Gott, der aus der Tiefe mich holt. Hymnologische Kommentare zu den Liedern im Ergänzungsheft zum Evangelischen Gesangbuch. Jan Janssen zum 60. Geburtstag. HEG 3/Ergänzungsheft, Göttingen 2023

XXmas: Macht gebären statt Macht gebaren. 1. Weihnachtstag (Christfest I) 2Mose 2,1-10 - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien VI/1)

Gewerblich-technische Lehrkräftebildung in Deutschland – Analyse der Einflüsse auf das akademische Selbstkonzept von Lehramtsstudierenden technischer (beruflicher) Fachrichtungen - Vernholz, Mats; Temmen, Katrin

Numerische Untersuchung von Oberflächenstrukturierung zur Erhöhung der Effizienz von Kissenplatten-Wärmeübertragern - Afsahnoudeh, Reza; Holzmüller, Maik; Bader, Fabian; Homberg, Werner; Kenig, Eugeny Y.

Housing situations and local COVID-19 infection dynamics using small-area data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik (Scientific Reports)
Abstract Low socio-economic status is associated with higher SARS-CoV-2 incidences. In this paper we study whether this is a result of differences in (1) the frequency, (2) intensity, and/or (3) duration of local SARS-CoV-2 outbreaks depending on the local housing situations. So far, there is not clear evidence which of the three factors dominates. Using small-scale data from neighborhoods in the German city Essen and a flexible estimation approach which does not require prior knowledge about specific transmission characteristics of SARS-CoV-2, behavioral responses or other potential model parameters, we find evidence for the last of the three hypotheses. Outbreaks do not happen more often in less well-off areas or are more severe (in terms of the number of cases), but they last longer. This indicates that the socio-economic gradient in infection levels is at least in parts a result of a more sustained spread of infections in neighborhoods with worse housing conditions after local outbreaks and suggests that in case of an epidemic allocating scarce resources in containment measures to areas with poor housing conditions might have the greatest benefit.
Keywords: Multidisciplinary

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Güldenpenning, Iris; Weigelt, Matthias; Böer, Nils Tobias; Kunde, Wilfried (Human Movement Science)
Typically, head fakes in basketball are generated to, and actually do, deteriorate performance on the side of the observer. However, potential costs at the side of the producer of a fake action have only rarely been investigated before. It is thus not clear yet if the benefit (i.e., slowed reactions in the observer) of performing a head fake is overestimated due to concurrently arising fake production costs (i.e., slowed performance in the producer of a head fake). Therefore, we studied potential head-fake production costs with two experiments. Novice participants were asked to generate passes to the left or right side, either with or without head fakes. In Experiment 1, these actions were determined by an auditory stimulus (i.e., a 440 Hz or 1200 Hz sinus or jigsaw wave). After an interstimulus interval (ISI) of either 0 ms, 800 ms, or 1500 ms, which served the preparation of the action, the cued action had to be executed. In Experiment 2, passing to the left or right, either with or without a head fake, was determined by a visual stimulus (i.e., a player with a red or blue jersey defending either the right or left side). After an ISI of either 0 ms, 400 ms, 800 ms, or 1200 ms, the cued action had to be executed. In both experiments, we observed higher reaction times (RTs) for passes with head fakes as compared to passes without head fakes for no and an intermediate preparation interval (from ISI 0 ms to 800 ms), but no difference for a long preparation interval (for an ISI of 1200 ms and 1500 ms). Both experiments show that generating fake actions produces performance costs, however, these costs can be overcome by a longer preparation phase before movement execution.
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

The Third Knowledge Dimension: From a Binary System to a Three-limbed Epistemology - Hagengruber, Ruth (Women Philosophers on Economics, Technology, Environment, and Gender History)
The thesis of this paper is that a new kind of epistemology evolves from the use of artificial intelligence. The path it takes changes our understanding of the world, of human values and also of science and will be irreversible. The question that arises is whether this form of intelligence also influences our knowledge structure. By this I mean the area that we outline philosophically as the epistemological area. So the question is, under these circumstances, is the way we gain knowledge today still comparable to the definitions that philosophy has provided us with for centuries? The answer is: No! The paper sketches in broad outlines what the cornerstones of change will be and what consequences this will have for our way of understanding.

Women Philosophers on Economics, Technology, Environment, and Gender History
In times of current crisis, the voices of women are needed more than ever. The accumulation of war and environmental catastrophes teaches us that exploitation of people and nature through violent appropriation and enrichment for the sake of short-term self-interest exacts its price. This book presents contributions on the currently most relevant and most urgent issues: reshaping the economy, environmental problems, technology and the re-reading of history from the non-western and western tradition. With an outlook into the problems of class, race and gender in its intersectional framing, the collection offers a unique overview of current research in these fields and contributes to the renewal and contemporary presentation of feminist thought from partly concrete perspectives with regard to factual issues.

Women Philosophers on Economics, Technology, Environment and Gender History. Shaping the Future – Rethinking the Past. - Hagengruber, Ruth Edith (Women Philosophers on Economics, Technology, Environment, and Gender History)

Das Aufbegehren der Eroberten. Absichten, Formen und Deutungen im europäischen Mittelalter (8. bis 14. Jahrhundert) - Kamp, Hermann (Eroberte im Mittelalter. Umbruchssituationen erleben, bewältigen, gestalten)

Minimizing Eye Movements and Distractions in Head-Mounted Augmented Reality through Eye-Gaze Adaptiveness - Wecker, Daniel; Yigitbas, Enes (Proceedings of the ACM Symposium on Spatial User Interaction (SUI 2023))

GaMoVR: Gamification-Based UML Learning Environment in Virtual Reality - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Gottschalk, Sebastian; Engels, Gregor (Science of Computer Programming)

Transitional Cross Reality Interfaces for Spatially Demanding Search and Collect Tasks - Schmidt, Leonard; Yigitbas, Enes (Proceedings of the 27th International Workshop on Personalization and Recommendation)